Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1080/13880200490510702
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Preliminary Antimalarial Activity ofHumiria balsamifera

Abstract: From stems and leaves of Humiria balsamifera St. (Aubl.) Hill (Humiriaceae) were isolated 6 triterpenes [arjunolic acid, 2b,3a-dihydroxy-D:A-friedooleanane, friedelin, a-and bamyrins and lupeol], a flavonol (quercetin), an isocoumarin (bergenin) a diterpene (phytol), and 2 phytosteroids (sitosterol and stigmasterol)]. Three sesquiterpenoids [caryophyllene oxide (0.9%), humulene epoxide II (0.3%) and trans-isolongifolenone (0.6%)], a diterpene [phytol (29.4%)] and four aliphatic esters [methyl tetra-(0.3%), hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…H. balsamifera is a large tree common in Amazonia and North-East Brazil. Numerous compounds were isolated from this species, including trans-isolongifolenone (Da Silva et al 2004). 48 Interestingly, a repulsive effect of this compound was described on Ae.…”
Section: Mrc5 Healthy Cell Line) Concurrently 3 Randomly Selected Exmentioning
confidence: 99%
“…H. balsamifera is a large tree common in Amazonia and North-East Brazil. Numerous compounds were isolated from this species, including trans-isolongifolenone (Da Silva et al 2004). 48 Interestingly, a repulsive effect of this compound was described on Ae.…”
Section: Mrc5 Healthy Cell Line) Concurrently 3 Randomly Selected Exmentioning
confidence: 99%
“…(Aubl.) Hill (Humiriaceae), a plant commonly found in South America (Da Silva et al 2004). Isolongifolenone is odorless and some of its derivatives have a characteristic woody smell (Hall 1973, Pickenhagen and Schatkowski 2002, De Bruyn et al 2003.…”
mentioning
confidence: 99%
“…Several studies have indeed documented the antimalarial potency of crude extracts from the genus Diospyros as well as that of some of their antimalarial constituents (Likhitwitayawuid et al, 1999;Ma et al, 2008;Kantamreddi and Wright, 2008), which were generally found to be triterpenes such as betulinic acid 3-caffeate from Diospyros quaesita (Ma et al, 2008) and naphthoquinones such as diospyrin from Diospyros montana (Likhitwitayawuid et al, 1999). Bergenin, an isocoumarin previously isolated from Diospyros sanza-minika (Musgrave and Skoyles, 1974) was found to be inactive against P. falciparum and only weakly active against P. berghei (Silva et al, 2004). Compound 1, a methyl derivative of bergenin, was inactive.…”
Section: Resultsmentioning
confidence: 98%